100 first things to know - Sirett,Dawn (London Dorling Kindersley, 2022)
Help your little one learn important vocabulary and build knowledge. From colours, shapes, and numbers, to science, art, nature, and weather this first word and picture book is filled with 100 useful things that will stimulate your baby or toddler's natural curiosity about the world around them. Part of an award-winning DK board book series that mixes engaging, real-life photos with entertaining illustrations, 100 First Things to Know has big, colourful, toddler-tough pages filled with things to talk about, learn about, and smile about! Every page is a visual treat, making this appealing board book great for sharing, and an attractive baby, toddler, or preschool gift. As they point to the pictures and say the words, little ones can identify lots of important things to know - they'll soon recognize colours, shapes, and patterns, count to 10, name different weathers and seasons, and learn some animal life cycles, as well as some useful maths and science things. And they'll be captivated by the delightful pictures, from five funny dinosaurs for the number five, to a cute snowman for snowy weather, and a big digger for the colour yellow. This beautiful picture book follows on from the award-winning 100 First Words and 100 First Animals (previous titles in this early learning series). Each title has inviting, look-and-point pictures that stimulate talking, and clear word labels that encourage naming and picture-and-word association, building language and reading readiness. Cleverly designed to inform and entertain, 100 First Things to Know takes your little one on an exciting learning adventure.
Keywords: General knowledge book